10(4k+6t+3)=

Simple and best practice solution for 10(4k+6t+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(4k+6t+3)= equation:


Simplifying
10(4k + 6t + 3) = 0

Reorder the terms:
10(3 + 4k + 6t) = 0
(3 * 10 + 4k * 10 + 6t * 10) = 0
(30 + 40k + 60t) = 0

Solving
30 + 40k + 60t = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + 40k + -30 + 60t = 0 + -30

Reorder the terms:
30 + -30 + 40k + 60t = 0 + -30

Combine like terms: 30 + -30 = 0
0 + 40k + 60t = 0 + -30
40k + 60t = 0 + -30

Combine like terms: 0 + -30 = -30
40k + 60t = -30

Add '-60t' to each side of the equation.
40k + 60t + -60t = -30 + -60t

Combine like terms: 60t + -60t = 0
40k + 0 = -30 + -60t
40k = -30 + -60t

Divide each side by '40'.
k = -0.75 + -1.5t

Simplifying
k = -0.75 + -1.5t

See similar equations:

| -1.5n-12=94 | | 4.4x-0.2=26.2 | | 0=7/2x-21/2 | | m/3=-27 | | 8x-31/6=x-5 | | y/18=64 | | (3x^2-4x)(2x^3+3x-1)=y | | 3(x-7)=(3x+2)(2x+1) | | 2u-u= | | p/3asfdr | | w/7.5=52 | | 5n=10-5n | | 3x(2x+7)= | | 9.8/1.4 | | 3/5-x | | 8s+7=9s | | 3(2z-10)=54 | | 4z-42=32-3 | | 2(7+11)+3(7)=57 | | 7x+x(x-5)=0 | | y-(-13)=4/3(x-(-11)) | | k/7=17 | | d-3=95 | | 14x-2(9-x)=0 | | log(7)*y=5x | | 4y-13=12 | | 113=-25 | | 3(x-4)+12=14 | | 114+t-29=7t+25 | | $10.03/$29.07 | | y=-16t^2+32t+8 | | 12m+5n-4m+10n= |

Equations solver categories